Texture and microstructural changes after thermal cycling of 6061Al-20vol%SiCw metal matrix composite: The role of microscopic internal stresses. (December 2022) - Eddahbi, M.; Fernández, R.; Llorente, I.; González-Doncel, G.
Abstract: The dramatic texture and microstructural changes observed in 6061Al-20vol%SiCw metal matrix composite undergoing severe thermal cycles, under the absence and the simultaneous action of an external tensile stress, are studied. Under only thermal cycles (100–450 °C) homogenization and disorientation of the SiC whisker reinforcement and crystallographic texture randomization occurs. However, when a simultaneous tensile stress is applied, the whiskers rotate so that their long direction aligns with the tensile axes. Furthermore, a strong texture and large deformations (superplasticity), higher than 1000%, are achieved. These results are explained on the basis of the microscopic stress fields generated at the different microstructural scales (stresses of type II and type III) and well-known observation of dislocation generation at the SiC-metal interface during the cooling period of the cycles. We propose that moving dislocations (responsible of type III stresses) operate differently under the absence or the presence of the external stress. Under no stress, dislocation motion (occurring mainly during the heating period) is driven only by the type II internal stress. However, dislocation motion is improved when an external stress is applied, leading to texture changes and large elongations. Despite that a low external stress is applied, it overcomes the effect of the internal stresses for dislocation motion. Graphical Abstract: ga1 Highlights: The changes related with the homogeneity/orientation of the reinforcement in Al-SiCw composite undergoing TC are discussed. TC leads to homogenization of the SiCw reinforcement. Dramatic SiCw reorientation with the tensile axis direction occurs when samples are strained under TC conditions. The microstructural changes are explained form the evolution/interaction of microscopic internal stresses raised during TC. Cooling period generates massive moving dislocations which are driven by the internal stress fields or the external stress.